Differential roles of ice crystal, endogenous proteolytic activities and oxidation in softening of obscure pufferfish (Takifugu obscurus) fillets during frozen storage. (25th April 2019) - Yang, Fang; Jing, Diantao; Yu, Dawei; Xia, Wenshui; Jiang, Qixing; Xu, Yanshun; Yu, Peipei
Highlights: Roles of ice crystal, proteolysis and oxidation were distinguished in frozen storage. Ice crystal contributed the most for fish softening during frozen storage. Inhibition of proteolysis and oxidation was beneficial for frozen fish texture. Fish softening during frozen storage was initially fast and then slowed down. Abstract: Obscure pufferfish ( Takifugu obscurus ) softening during frozen storage remains to be solved. This study was therefore aimed to provide explanations by differentiate the roles of three potential factors in fish softening. The influences of ice crystal, endogenous proteolytic activities, and oxidization were distinguished by treatment of fish fillets with liquid nitrogen, iodoacetic acid, and tea polyphenol with ascorbic acid, respectively. This distinguishing method was verified to be effective by investigation in ice crystal microstructure, endogenous proteolytic activities and lipid and protein oxidation. In comparison of three factors, it showed that the shear force of fish fillets with smaller ice crystals was about 15.5% and 13.7% higher than those with the inhibition of endogenous proteolytic activities and oxidation respectively, indicating the dominant role of ice crystal in frozen fish softening. Besides, quality decline of frozen fish was initially fast and then slowed down during the storage.